UTILIZING THE BALANCED SCORECARD TO MANAGE THE SUSTAINABLE DEVELOPMENT OF ENTERPRISES - Zhang, Qin (Sworld-Us Conference proceedings, 2025)
This study explores the application of the Balanced Scorecard (BSC) in corporate Sustainable Development (SD) management against the backdrop of global economic integration and worsening environmental issues. By combining literature research, case analysi